1950
DOI: 10.1172/jci102295
|View full text |Cite
|
Sign up to set email alerts
|

Lung Ventilation Patterns Determined by Analysis of Nitrogen Elimination Rates; Use of the Mass Spectrometer as a Continuous Gas Analyzer 1

Abstract: A quantitative measure of the effectiveness of lung ventilation and the significance of unequal mixing of the gases in the lung is of interest in many problems such as the measurement of lung volume and in studies of such processes as tissue denitrogenation which involve transport of gases through the lung.The present study involves the determination of the turnover rates attained in the lung from measurements of the rate at which nitrogen is washed out of the lungs while the subject is breathing pure oxygen. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
1
1

Year Published

1952
1952
2001
2001

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(47 citation statements)
references
References 14 publications
(12 reference statements)
3
42
1
1
Order By: Relevance
“…This is in contrast with data obtained by continuous analysis reported here and by Robertson, Siri, and Jones (12). However, one of several requirements upon which experiments were rejected or accepted was the "definiteness of linear relationship between y and n"; that is, the definiteness with which the clearance process could be described by a single value of w. As Robertson points out, analysis of multiphasic pulmonary clearance or equilibration curves with equations containing only one exponential term (4,6,10) is inadequate and may lead to ambiguous or at times incorrect interpretation of the nature of ventilatory inefficiency (23,26).…”
Section: Comparison Of Methodscontrasting
confidence: 99%
See 2 more Smart Citations
“…This is in contrast with data obtained by continuous analysis reported here and by Robertson, Siri, and Jones (12). However, one of several requirements upon which experiments were rejected or accepted was the "definiteness of linear relationship between y and n"; that is, the definiteness with which the clearance process could be described by a single value of w. As Robertson points out, analysis of multiphasic pulmonary clearance or equilibration curves with equations containing only one exponential term (4,6,10) is inadequate and may lead to ambiguous or at times incorrect interpretation of the nature of ventilatory inefficiency (23,26).…”
Section: Comparison Of Methodscontrasting
confidence: 99%
“…First Tables I and II, based on multiphasic analysis of -pulmonary N2 elimination rates (12). However, we prefer to treat alveolar ventilation as a discontinuous rather than as a continuous process, as they have done.…”
Section: Comparison Of Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Veff is converted to BTPS (Veff-BTPS) [24]. The switching errors above FRC should be corrected for by subtracting any volume above EEL (previously converted to BTPS conditions) from the VEFF-BTPS to obtain FRCN 2 [7,12]:…”
Section: Calculationsmentioning
confidence: 99%
“…The study of the elimination of an inert gas from the lungs of human individuals has proven a useful tool in the determination of ventilation patterns (1,2). In particular it could be demonstrated that the lungs of emphysematous patients can be conceived as being composed of at least two different compartments, i.e., a relatively small space with good ventilation and a relatively large space with poor ventilation (3).…”
mentioning
confidence: 99%